The Characterization Of Some Physical And Mechanical Properties Of Medium Density Particleboard Made From Oil Palm Trunk Without Formaldehyde Based Adhesives - Boon, Jia Geng (2014)

(untitled)
This research characterized some properties of oil palm trunk particleboard made without formaldehyde based adhesives. The processing parameters including hot pressing temperature, hot pressing time and hot pressing pressure to produce oil palm trunk particleboard using coarse size particles (sieved with No. 10 filter) were studied. Penyelidikan ini mencirikan sebahagian sifat sifat papan serpai batang kelapa sawit diperbuat tanpa pengikat berasaskan formaldehid. Parameter pemprosesan termasuk suhu mampatan panas, jangkamasa mampatan panas dan tekanan mampatan panas untuk menghasil papan serpai batang kelapa sawit yang partikel saiz kasar (disaring dengan penapis No. 10) telah dikaji.